2019
DOI: 10.3390/coatings9110763
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Study of Gas Molecule Adsorption on C-doped Zigzag Phosphorene Nanoribbons

Abstract: Phosphorene, due to its large surface-to-volume ratio and high chemical activity, shows potential application for gas sensing. In order to explore its sensing performance, we have performed the first-principles calculations based on density functional theory (DFT) to investigate the perfect and C-doped zigzag phosphorene nanoribbons (C-ZPNRs) with a series of small gas molecules (NH3, NO, NO2, H2, O2, CO, and CO2) adsorbed. The calculated results show that NH3, CO2, O2 gas molecules have relatively larger adso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Several types of 2D MXene materials with M 2 X, M 3 X 2 , and M 4 X 3 stoichiometry have been synthesized using fluorine and hydrogen from precursor MAX phases and found to exhibit large surface areas in the range of 250–1000 m 2 g –1 . Interestingly, MXenes possess high adsorption energies when compared to other 2D materials, as shown in Figure . Zhang et al studied O surface-functionalized MXene Ti 2 C (Ti 2 CO 2 ) and found enhanced photocatalytic performance for CO 2 reduction to formic acid. Later, Li et al theoretically observed M 3 C 2 -type (Mo 3 C 2 and Cr 3 C 2 ) MXenes as most promising candidates for CO 2 conversion into hydrocarbon fuels …”
Section: Introductionmentioning
confidence: 99%
“…Several types of 2D MXene materials with M 2 X, M 3 X 2 , and M 4 X 3 stoichiometry have been synthesized using fluorine and hydrogen from precursor MAX phases and found to exhibit large surface areas in the range of 250–1000 m 2 g –1 . Interestingly, MXenes possess high adsorption energies when compared to other 2D materials, as shown in Figure . Zhang et al studied O surface-functionalized MXene Ti 2 C (Ti 2 CO 2 ) and found enhanced photocatalytic performance for CO 2 reduction to formic acid. Later, Li et al theoretically observed M 3 C 2 -type (Mo 3 C 2 and Cr 3 C 2 ) MXenes as most promising candidates for CO 2 conversion into hydrocarbon fuels …”
Section: Introductionmentioning
confidence: 99%
“…[ 211 ] Other similar studies based on DFT calculations have been also carried out to check the H 2 capture ability of phosphorene. [ 212–216 ]…”
Section: Applications Of Bp‐based Materials In Energy and Catalysismentioning
confidence: 99%
“…However, the development of two-dimensional materials is restricted by the high diffusion barriers and the low cycling stability [9,20]. Doping metal elemental, such as Cr [21], Ru [22], Zn [23], Sr [24], and nonmetal elemental, such as C [25], N [26], B [27] are typical strategies to enhance the properties of electrode materials [28]. Moreover, nitrogen doping is an effective way to enhance metal-semiconductor transition and electronic conductivity due to strong electronegativity and similar atomic radius to carbon [29][30][31].…”
Section: Introductionmentioning
confidence: 99%